The Effect of The Development Results of Teaching Materials, Research, and Teaching Methodologies on The Learning Outcomes and Student's Write Research Proposals Ability - Nur Ihsan HL; Nasruddin Nasruddin; Andri Estining Sejati (Postgraduate, University of Mataram, 2025)
Development results need to be further researched to determine the effects on learning, such as in the development of teaching materials that were experimented with learning outcomes and other related abilities. The research aims to determine the influence of applying the development of teaching materials, research, and teaching methodologies results on learning outcomes and student's ability to write research proposals. The research was a quasi-experimental type with a nonequivalent control group design. The subject was the S1 Mathematics Education, FKIP, USN Kolaka. Research instruments on learning outcomes with essay questions and the ability to write proposals with the PKM-R Simbelmawa rubric. Data collection by tests, demonstrations, and documentation, then analyzed with parametric inferential statistics through the MANOVA test. The research results showed the significant value of teaching materials with learning outcomes of 0.000 and the application of teaching materials to students' ability to write research proposals of 0.000. This shows that applying the results of developing teaching materials, research, and teaching methodologies affects learning outcomes and the ability to write student research proposals. The material and summary in the teaching materials add to students' insight and independence in finding knowledge related to the material in the mathematics research methodology course. The exercises billed in the teaching materials make students easier to practice writing research proposals.